LINGUISTIC FEATURES OF COLLOQUIAL SPEECH - Koval, O.V. (PUBLISHINGS of Kostanay State Pedagogical University, 2019)
The article is devoted to the place of colloquial speech in modern Russian. The purpose of the article is to consider the characteristics of conversational speech. The author of the article studies the concepts of colloquial speech that exist in modern linguistics. This article attempts to identify the extralinguistic and linguistic signs of colloquial speech. Particular attention is drawn to the features of colloquial speech: phonetic, lexical, morphological, syntactic. The author comes to the conclusion that, unlike book speech, colloquialism does not have a strict codification, it has a number of language features and norms.
Keywords: language; communication; speech; norm; sign; style